Analysis Of Consumer Perception Of Using Digital Payment In The Perspective Of Maqashid Syariah (Case Study Of Generation Z Users Of Go-Pay) - Nasution, Inayatul Widad; Batubara, Maryam; Ridwan, M. (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2017)
This research aims to analyze the perceptions of Generation Z consumers in using digital payment systems, particularly GoPay, from the perspective of Maqashid Syariah. This study examines how factors such as security, trust, convenience, and user experience influence consumer decisions in using GoPay. The research method used is quantitative with a descriptive approach. Data were collected through a survey using purposive sampling techniques from respondents among Generation Z who actively use GoPay as a digital transaction tool. The data processing process using SPSS 25. The research results show that the principles of maqashid sharia such as hifz al-nafs, hifz al-mal, hifz al-din, and hifz al-‘aql play an important role in the decision to use GoPay. Additionally, the variables of security, trust, and convenience significantly influence user decisions, while the experience variable shows a significant impact. In the perspective of Maqashid Syariah, the use of GoPay can support more efficient and secure transactions in accordance with Sharia principles, as long as it maintains transparency and avoids elements of usury. Keywords: Security Perception, Trust Perception, Ease Perception, User Experience Perception, Consumer Usage Decision, Maqashid Sharia, GoPay.